Confronting Partner Violence: An Educational Program Using the Moodle Platform - Loyola Quistial, Sonia Beatriz (2024)
The consequences of violent attitudes are worrying for society, the educational system in its task of training new generations must have as its main objective to reduce gender violence, for this reason this research arises that attempts to reduce violent attitudes among peers. This work presents the results after due analysis, whose objective is to demonstrate that the Moodle educational platform improves attitudes about intimate partner violence in students of Educational Institutions, generating changes through the page if it hurts is not love For the students of the First year of parallel Baccalaureate A of the Clemencia Rodríguez de Mora Educational Unit of the City of Santo Domingo, Ecuador, an investigation was carried out on the current state of violence committed and violence suffered, and their relationship in the gap that exists in the management of the inclusive Education System Model. Regarding the methodology, a quantitative approach is used, quasi-experimental design, the technique used was the questionnaire, the type of research is descriptive. Finally, in conclusion, it was evident that it is feasible to create didactic activities through the Moodle educational platform with the name Si Duele no es Amor, where students are nourished and express the desire to learn about different types of violence, as well as also detect and avoid attacks produced by the social environment, for this reason both teachers and authorities are ready to collaborate and provide timely help to correctly develop the proposal.